Integrasi Tradisi dan Modernisme dalam Sistem Kesehatan Masyarakat Kampung Naga: Studi Kasus Perilaku Pengobatan dan Hidup Bersih Sehat - Nurochmah Nurochmah; Suidat Suidat; Salwa Marsela; Suryamin Suryamin; Muhammad Sarkhosyi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Kampung Naga, as one of the traditional villages in Indonesia, has a unique health system. In an effort to preserve their culture, the people of Kampung Naga remain open to modern developments. This research analyzes how the community of Kampung Naga integrates traditional medicine practices with modern healthcare services. Through a qualitative approach focusing on medicinal behavior and clean and healthy living practices, the study reveals a coexistence between the use of herbal medicines, prayers, and visits to healthcare facilities. There are several challenges in this adaptation process, such as limited access to healthcare facilities and a lack of understanding regarding the importance of clean and healthy living practices. Further analysis indicates that cultural factors, beliefs, and the availability of modern healthcare services also influence the community’s medical behaviors. The findings have significant implications for developing public health programs in culturally diverse regions. Such programs need to be designed with consideration of local cultural values and involve the community actively in planning and implementation.